KONSELING BEHAVIORAL DALAM MENGATASI PERILAKU AGRESIF ANAK USIA DINI - Ismailia Muwaffaqoh Arifah; Anggraini Widyastuti (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2018)
This study discusses four ways of learning in behavioral counseling in overcoming the aggressive behavior of early childhood. Aggressive behavior is not only possessed by adults, but early childhood can get seeds to do this maladaptive behavior. Over time, children become very potential to carry out various behaviors that can endanger both themselves and others. Early understanding is important to anticipate aggressive behavior. Children's mistakes in learning and interacting in their environment need to be considered because they are a major factor in shaping aggressive behavior.